1982
DOI: 10.1038/bjc.1982.159
|View full text |Cite
|
Sign up to set email alerts
|

The site of binding of anti-CEA antibodies to tumour CEA in vivo: an immunocytochemical and autoradiographic approach

Abstract: Summary.-Radiolabelled affinity-purified antibody to carcinoembryonic antigen (CEA) was injected i.v. into immune-suppressed mice carrying xenografts of human breast carcinoma. Its distribution in the tumours was examined by a combination of immunocytochemistry and autoradiography. The antibody interacted predominantly with the CEA in the extracellular tumour space, rather than on the cell membrane or cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Autoradiographic techniques in s.c. tumors and lymph node metastases have also been carried out by several authors [25,30,31,33] as well as immunoperoxidase techniques [13,21]. Nearly all authors found preferential localization in the periphery of tumors which usually is the most vascular.…”
Section: Itemmentioning
confidence: 98%
“…Autoradiographic techniques in s.c. tumors and lymph node metastases have also been carried out by several authors [25,30,31,33] as well as immunoperoxidase techniques [13,21]. Nearly all authors found preferential localization in the periphery of tumors which usually is the most vascular.…”
Section: Itemmentioning
confidence: 98%
“…But, the fact that radiolabeled antibodies accumulate in the tumor site does not necessarily mean that the antibodies localize on the surface of tumor cells. Moshakis et al (1982) examined the site of binding of the injected anti-CEA antibody to the tumor CEA by a combination of immunocytochemistry and autoradiography and reported that the antibody was predominantly in extracellular spaces rich in CEA surrounding a xenografted human breast cancer in immunosuppressed mice. Kim et al (1980) considered that AFP producing tumors had an extracellular milieu of AFP which would provide a gradient between tumor and non-tumor adjacent tissues and this condition, thus, made radioimmunodetection possible, although AFP is a cytoplasmic tumor marker.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, monoclonal antibodies (mAbs) recognizing tumour-associated antigens have been successfully applied as carriers of radionuclides [2], toxins [5] or cytostatic agents [14]. The antitumour effects appear to be limited because of the relatively low concentration of the cytotoxic reagent delivered to tumours [12].…”
Section: Introductionmentioning
confidence: 99%